Effect of Bungur Leaf Extract on Glucose Reduction in Kidney Dysfunction Rats - Firelza Nabhaki; Indri Meirista; Rahmadha Trifah (International Journal of Health Engineering and Technology, 2026)
Diabetes mellitus is a metabolic disorder with an increasing prevalence in Indonesia, including in the city of Jambi. Conventional antidiabetic therapies such as metformin, sulfonylureas, and insulin are effective in lowering glucose levels, but long-term use can cause side effects, including the risk of kidney damage. Bungur leaves (Lagerstroemia speciosa) contain flavonoids, alkaloids, tannins, triterpenoids, and corosolic acid, which have potential antihyperglycemic and nephroprotective properties. This study aimed to evaluate the effects of bungur leaf ethanol extract on blood glucose levels and kidney function in male white rats induced with alloxan and gentamicin. The study was conducted experimentally with seven treatment groups. The parameters observed included blood glucose and serum creatinine levels. The results showed a significant decrease in glucose, with the highest effectiveness at a dose of 1200 mg/kgBW. The extract also lowered creatinine levels, indicating a renal protective effect. These findings suggest the potential of crape myrtle leaves as a herbal antidiabetic agent while maintaining renal function